KEPEMIMPINAN KEPALA SEKOLAH DI ERA DISRUPSI - Yulizar Yulizar; Farida Farida (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Disruption phenomenon, the situation where in movement the world of industry  or work rivalry does not linear. The changes are very quick, fundamental with mess up the pattern of old arrangement to create the new arrangement. Disrupsi initiated the birth of a new business model with a strategy more innovative and disruptive. The scope of the changes ranging from the business world,banking, transportation, social community, until education. This area will demand us to changes and follow the development of the times. The purpose of this research to find out how the headmaster in the disruption era. This research used qualitative approach with the collecting data technique is observation interview and documentation. The research result showed that many aspect contribution toward the quality of education one of basic is ability from each headmaster in bring out management at school who he leads in planning, organizing, mobilization, and monitoring activity so that all of scholl substance held good. The leadership of headmaster is very important in manage an institution. Because of that headmaster must develop his self and able to implement fuctions of management and leadership.